An Overview on Leishmania Diagnosis - Hossein Rezvan; Ali reza Nourian; Sahar Hamoon Navard (Pasteur Institute of Iran, 2017)
Leishmaniasis is now accounted as a health problem and categorized as a class I disease (emerging and uncontrolled) by World Health Organization (WHO), causing highly significant morbidity and mortality with different clinical presentations. The incidence of human leishmaniasis is increasing and its geographic distribution in humans and animals is shown to be wider than estimated before. Indeed, more than 350 million people are at risk of Leishmania infection, and about 1.6 million new cases occur causing more than 50 thousand death annually. Control of leishmaniasis is highly dependent to the early diagnosis and treatment of the disease. In recent years, there have been advances in diagnosis of Leishmania infection. However, the main challenge in Leishmania diagnosis is the lack of a gold standard test in order to establish an effective strategic program to control and eradicate the disease. This review provides the latest information regarding the diagnosis of the disease, which is based on a combination of clinical features (supported by epidemiologic data) and laboratory tests including direct parasitological (microscopy, histopathology, and parasite culture), serological and molecular tests.